Strategi Guru Bahasa Indonesia dalam Menerapkan pembelajaran Blended Learning di SMP Se-Kecamatan Peranap - Viora, Viora (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
This research is entitled "Strategy of Indonesian Language Teachers in Implementing Blended Learning in Junior High Schools in Peanap District", this study will discuss strategies by teachers in schools regarding blended learning at the SMP level in Peranap District. The formulation of the problem of this research is How is the strategy of Indonesian language teachers in implementing blended learning in SMP, Peranap District?. The purpose of the study was to determine the strategy of Indonesian language teachers in blended learning in SMP in Peranap sub-district. This research method is a case study. The research approach is qualitative. Data collection techniques are in-depth interviews and documentation. The data analysis technique uses case study techniques or steps, including: 1) Category collection. 2) Direct interpretation. 3) Forming patterns and looking for equivalence between two or more categories. 4) Develop naturalistic generalizations through data analysis. The results of the research from the blended learning strategy are a combination of two or more learning strategies and methods to get the learning outcomes expected by the teacher. The blended learning strategy in learning Indonesian has 4 dimensions or components that are mixed into a unified form of learning. The strategies of Indonesian language teachers in blended learning are: 1) Youtube. 2) Videos. 3) Recording. 4) Learning materials and 5) Whatsapp.